KEDUDUKAN PEREMPUAN DALAM Al-QURAN DAN HADIS - Mistiani, Wiwin (Pusat Studi Gender dan Anak, IAIN Palu, 2019)
Islam is a religion that highly respects and values ​​women. Islam erases the Jahiliyah tradition which is so discriminatory towards women, in Islam men and women are considered to be equal, free-tackled, and even complementary and needy creatures of God. Islam as rahmatan lil Alamin positions women in a noble place. There is no dichotomy and discrimination between men and women. Al-Qur’an teaches the position of believers both men and women are equal before God, therefore they must obtain equal status in the eyes of God, and both have been declared the same as getting God’s grace. The departure of women to study even without mahram can be justified as long as their honor and safety are guaranteed and does not invite disobedience. Women have the right to work as long as they need it or the job needs it and as long as religious and moral norms are maintained. Therefore there is no obstacle for women to work as long as the work is carried out in an atmosphere of respect, courtesy, and they can maintain their religion and can also avoid negative impacts on themselves and the environment. Ignoring women and not involving them in activities that benefit the community means wasting at least half of the community’s potential.